FULMINANT ACUTE PANCREATITIS: HOW TO IMPROVE SURGICAL OUTCOMES IN THE PHASE OF ENZYMATIC TOXEMIA - E. A. Korymasov; M. Yu. Khoroshilov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2020)
In patients with progressive severe acute pancreatitis (SAP), early surgery is the last opportunity to influence the dismal outcome. The use of extracorporeal detoxification (ECD) methods along with a traditional surgical approach does not improve the outcomes of early surgeries in patients with progressive SAP due to the late elimination of aggression factors, as well as due to constant reabsorption of enzymatic toxic exudate from non-drained areas of the retroperitoneal space, abdominal cavity, and omentum. Preventive use of ECD (plasma exchange) can improve the outcomes of early surgeries in patients with fulminant SAP.